2011
DOI: 10.1103/physrevlett.106.188302
|View full text |Cite
|
Sign up to set email alerts
|

Axial Thermal Rotation of Slender Rods

Abstract: Axial rotational diffusion of rodlike polymers is important in processes such as microtubule filament sliding and flagella beating. By imaging the motion of small kinks along the backbone of chains of DNA-linked colloids, we produce a direct and systematic measurement of axial rotational diffusivity of rods both in bulk solution and near a wall. The measured diffusivities decrease linearly with the chain length, irrespective of the distance from a wall, in agreement with slender-body hydrodynamics theory. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…For qualitative study, we make a Rouse dynamics simplification and assume local isotropic drag using slender-body theory [34] ~2 /log 2 / ~ , and ignore long range hydrodynamic interactions. The fluid viscosity, measured to be η = 0.0022 kg/m•s, is used to account for the near wall effect [35]. To calculate the internal stresses caused by the conservative forces, we utilize the principle of virtual work [36,37].…”
Section: Theorymentioning
confidence: 99%
“…For qualitative study, we make a Rouse dynamics simplification and assume local isotropic drag using slender-body theory [34] ~2 /log 2 / ~ , and ignore long range hydrodynamic interactions. The fluid viscosity, measured to be η = 0.0022 kg/m•s, is used to account for the near wall effect [35]. To calculate the internal stresses caused by the conservative forces, we utilize the principle of virtual work [36,37].…”
Section: Theorymentioning
confidence: 99%
“…Rotational diffusion of micrometersized ellipsoids can be monitored through their orientation, where it is found that in quasi two-dimensional confinement, the anisotropy of diffusion is strongly affected [16]. Two-dimensional rotational diffusion of micron-sized rods consisting of DNA-linked spherical colloids has been probed by direct imaging [17]. The measurement of rotational diffusion of spheres is much more complicated.…”
mentioning
confidence: 99%
“…Experimentally, it is difficult to observe the near-wall Brownian motion of the slender particle with conventional optical methods because of complicated light scatterings. Particularly, a direct visualization of the minute change of the inclined angle between the moving particle and the surface has been elusive [14,17] and previous works typically assumed the particle being parallel to the wall [12,25]. In this work, we report an experimental study of the Brownian motion of nanowires tethered on a substrate.…”
Section: Introductionmentioning
confidence: 99%